The renovation of urban centres as an ideological practice (Ciudades, 2018)
The methodological positions adopted towards the possible ways of approaching the knowledge of what, in general terms, we can qualify as the question of the urban centres, and more precisely the area of the historic centres, has been decanted into two points of view, at least, that are the reflection, in time, of many other (ideological) positions referred to the idea of the city that derive from the both of them.
Keywords: urban centres; ideological practice